Assessing the validity of two-dimensional carotid ultrasound to detect the presence and absence of a pulse. (December 2020) - Sanchez, Stephen; Miller, Matthew; Asha, Stephen
Abstract: Background: Traditional assessment of return of cardiac output in cardiac arrest by manual palpation has poor accuracy. Point of care ultrasound of a major artery has been suggested as an alternative. We conducted a diagnostic accuracy study of two-dimensional carotid ultrasound to detect the presence or absence of a pulse, using cardiopulmonary bypass patients for pulse and pulseless states. Methods: A cross-sectional multi-patient, multi-reader repeated measures diagnostic study was conducted. For patients undergoing routine cardiopulmonary bypass, a portable ultrasound was used to record four 10-s videos the common carotid artery, three aimed for a pulse in high (>90 mmHg), medium (70−90 mmHg) and low (<70 mmHg) systolic blood pressure (SBP) ranges, and a pulseless video was recorded on cardiopulmonary bypass. Critical care physicians viewed the videos and were asked to nominate within 10 s if a pulse was present. True pulse-status was determined via the arterial-line waveform. Results: Twenty-three patients had all four videos collected. Median patient age was 64 (IQR 14), sixteen were male (70%) and median BMI was 27. The median SBP in high-, medium- and low-SBP groups were 120 mmHg, 83 mmHg and 69 mmHg respectively. Forty-six physicians reviewed a subset of 24 videos. Overall sensitivity was 0.91 (95% confidence interval 0.89−0.93) and specificity 0.90 (95% CI 0.86−0.93). Sensitivity was highest in the high-SBP group (0.96, 95% CI 0.93−0.98) and lowest in the low-SBP group (0.83, 95% CI 0.78−0.87). Conclusion: 2D ultrasound of the common carotid artery is both sensitive and specific for detection of the presence or absence of a pulse.